An analysis on the relationship between work family conflict and turnover intention: a case study in a manufacturing company in Malaysia - Long, C. S. (2016)
This study provide an insight of the relationship between work family conflict and turnover intention. Juggling between work and family are not something easy in life because individual need to be more sensitive in classify priority of work and life. If they are failing to manage their life properly, they will tend to involve in work-family conflict. Therefore, this exploratory study look into the factors in the work family conflict that affect turnover intention among employees in one manufacturing company in Malaysia.